Development and characterization of novel chitosan emulsion films via pickering emulsions incorporation approach. (January 2016) - Shi, Wei-Jian; Tang, Chuan-He; Yin, Shou-Wei; Yin, Yan; Yang, Xiao-Quan; Wu, Lei-Yan; Zhao, Zhen-Gang
Abstract: Microstructure heterogeneity of emulsion films impaired their physical performances. This work attempted to fabricate novel high-barrier chitosan (CH) emulsion films by manipulating emulsion's interface architecture via Pickering stabilization approach. Some selected physical properties, including tensile property, water vapor permeability (WVP), and oxygen permeability (OP) as well as the microstructure of the films were evaluated. Film-forming emulsions (FFEs) based on zein/chitosan colloid particles-stabilized Pickering emulsions (ZCCPEs) were extremely stable, evidenced by the similar droplets size and size distribution in the FFEs and film matrix, endowing the films with homogeneous distributions of lipid droplets over their 3D network matrix. Interestingly, emulsion films exhibited excellent oxygen-barrier efficiency, and the OP of the films was decreased by 1−4 orders of magnitude when compared with CH films. This phenomenon may be associated with the novel interfacial architecture of ZCCPEs as well as film microstructure morphology based on ordered assembles of CH matrix and ZCCPEs. A schematic diagram for the formation pathway of ZCCPEs-loaded CH emulsion films was proposed to establish structure-function relationships of the films. This study opens a promising pathway for producing emulsion films with excellent oxygen-barrier capability via Pickering stabilization principle. Graphical abstract: A schematic illustration of the formation pathway of novel CH emulsion films via Pickering emulsion approach. Highlights: A schematic illustration of formation pathway of ZCCPE-loaded CH films was proposed. Film-forming Pickering emulsions (ZCCPEs) were extremely stable. ZCCPES and films matrix presented similar droplet size and size distribution. ZCCPEs additions decreased the OP of CH films by 1−4 orders of magnitudes. The structure-function relationships of ZCCPE-loaded CH films was established.